About the conference dedicated to the 100th anniversary of A.I. Mesheryakov - Basilova, T.A.; Suvorov, A.V. (Klinicheskai͡a︡ i spet͡s︡ialʹnai͡a︡ psikhologii͡a, 2024)
On December 19, 2023, the National Scientific and Practical conference with international participation "Comprehensive support for children and young people with disabilities with complex sensory and multiple developmental disorders (To the 100th anniversary of Alexander Ivanovich Meshcheryakov)" was held at the A.I. Meshcheryakov Family Center, Sergiev Posad, Russia. The reports presented at the conference highlighted the current problems of studying complex developmental disorders and contributed to the exchange of experience between the conference participants in organizing and providing assistance to children and adults with congenital complex sensory and multiple developmental disabilities. 19 декабря 2023 года в г. Сергиев Посад в «Семейном центре им. А.И. Мещерякова» состоялась Всероссийская научно-практическая конференция с международным участием «Комплексное сопровождение детей и молодых инвалидов со сложными сенсорными и множественными нарушениями развития (К 100-летию Александра Ивановича Мещерякова)». Доклады, представленные на конференции, осветили современные проблемы изучения комплексных нарушений развития и способствовали обмену опытом между участниками конференции в вопросах организации и оказания помощи детям и взрослым с врожденными сложными сенсорными и множественными недостатками в развитии.